THE IMPACT OF THE CRISIS ON EDUCATION: analysis of educational projects for the 0-6 age group and the perspective of the educational centers (children’s poles) in Italy - Benvenuto, Guido; Corsi, Nadia; Sposetti, Patrizia; Szpunar, Giordana (Momento - Diálogos em Educação, 2021)
The pandemic emergency has forced girls and boys to adapt to completely changed living conditions (closure of schools, confinement at home, social distancing). At the same time, the 0-6 educational services found themselves re-modulating programming and planning to ensure the right to education, learning, and psychological well-being needs of girls and boys. However, the period of distance learning has amplified the obstacles to equity in education, conditioned by educational poverty and socio-cultural disadvantages. The contribution, after presenting the main field researches that have multiplied in Italy in this last year, will focus on the initiatives promoted in the first period of the health emergency (March-June 2020) from the infant-toddler centers and preschools of Roma Capitale. The most important novelty of the new legislative decree (number 65) are the Childhood Centers, which host educational services for girls and boys in both the 0-3 and 3-6 age segments in a single building or in neighboring buildings, for a better use of resources through the sharing of services, spaces and tools. The contribution presents the results of the first phase of analysis of the more than 430 distance learning projects carried out in the municipal educational services of Rome between March and July 2020, collected by the Department of Educational and School Services of Rome. The data collected show the ways in which the services have managed to rethink, with different strategies and tools, relationships with girls, boys and their families and educational activities, ensuring the continuity of relationships and learning processes.